FORGIVENESS AS SOLIDARITY IN CHRISTIAN EDUCATION BASED ON JOHANN BAPTIST METZ - Sopiani Sopiani; Dini Dini; Rorin April Nadiya; Retno Natanae; Eva Inriani (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2023)
This paper discuss the role of forgiveness in the Christian context as sign of solidarity and a duty in building loving and peaceful relationships. In the teachings of the Bible, forgiveness is a central principle and a strong calling for Christians. The words and examples in the Bible underscore the importance of forgiveness as an integral part of a life of faith. Forgiveness is not just an individual act, but also carries a deeper meaning in the context of social relationships, both between individuals and community groups. Forgiveness shows solidarity, empathy, and deep love in establishing healthy and constructive relationships. In addition, Christianity also emphasizes the importance of forgiveness as the responsibility of believers in following Christ's example. In forgiving, Christians demonstrate the character of Christ who forgives and gives new opportunities. Forgiveness also creates an environment that encourages reconciliation, peace and social transformation. In this context, Christians have an active duty in promoting forgiveness, repairing broken relationships, and creating a society filled with love and peace. The practical implication of this view is the importance of engaging in the process of forgiveness, avoiding vengeance and retaliation, and committing to building relationships based on mutual understanding, forgiveness, and repair. In conclusion, forgiveness in.